General training, government responsibility and the rural unemployed - Henderson, Ian G. (Statistical and Social Inquiry Society of Ireland, 1973)
"The least mobile variable factor of production, labour, is nowadays also the least important. The factors of production which matter are all now highly mobile." This contentious statement by a well-known journal,highlights one of the problems of an economy which claims labour as its main natural resource. If labour does not matter then prospects for such an economy are bleak, but on the other hand, if the other factors are highly mobile, then emigration need not be the life-blood of such a place. Manpower may well be the least important factor yet if the work-force of an area is of a lower calibre than the average for the country, that area is at a distinct disadvantage if it hopes to attract new industry. This is the problem that must be faced in the rural areas of Northern Ireland. This paper will consider two aspects of the question. First, it will look for a theoretical justification for Government intervention in this field. Secondly, it will examine the results of a study of a general training course held at Enniskillen Government Training Centre, to see if such training is both feasible and worthwhile.
Read before the Society, 13 December 1972
Keywords: Training; Rural unemployment; Human capital; 314.15